The Relationship Between Organizational Culture and Employees' Satisfaction Shown on the Example of Tourism Businesses in Montenegro - Olivera Simovic; Djurdjica Perovic; Milica Raicevic (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Organizational culture, as an area of management is a complex system of mutual values that creates an organization's identity and makes it different from the competition. The aim of this paper is to create an adequate approach for improving competitive advantages and better performance of Montenegro's tourism businesses through improving business environment as one of the competitiveness factors. Through this work, the relationship and influence between the type of organisational culture and employees' satisfaction is being determined and analysed through different dimensions of the work they are doing. For the needs of this work a quantitative explorative research has been done, using the method of questionnaire. In the questionnaire, the Organizational Culture Assessment Instrument (OCAI) and the Test for measuring employees' satisfaction have been used. The obtained results show us the type of organizational culture that is characteristic for tourism businesses in Montenegro, as well as the influence it has on the level of employees' satisfaction, through different dimensions. Business environment that increases the level of job satisfaction of employees contributes to loyalty and achieving better results in tourism businesses.
Keywords: L29; 330; organizational culture; management; employees' satisfaction; tourism businesses